Cell-mediated immunity to gluten within the small intestinal mucosa in coeliac disease. Issue 2 (February 1982) - Howdle, P D; Bullen, A W; Losowsky, M S
Abstract : Jejunal biopsies from controls and coeliac patients were maintained in organ culture in the presence of gluten fraction III. The culture media were assayed for evidence of lymphokine activity in a migration inhibition test using normal peripheral blood leucocytes. Significant inhibition of migration was produced by media from untreated coeliac patients compared with controls (P less than 0.005) or treated coeliac patients (P less than 0.001), indicating the production of a leucocyte migration inhibition factor (LIF) by untreated coeliac mucosa in response to gluten fraction III. The degree of inhibition correlated with the preculture interepithelial lymphocyte count in the coeliac biopsies (P less than 0.02). In six coeliac patients studied when on a normal diet and on a gluten-free diet, LIF was produced while on a normal diet, but not while on a gluten-free diet. These results suggest that a local cell-mediated immune reaction to gluten is present in the mucosa of patients with untreated coeliac disease but that this is reversed by treatment with a gluten-free diet.